Preeclampsia in the Modern Era: New Insights from Global Research and Implications for Practice in Indonesia - Arya Ady Nugroho; Yudianto Budi Saroyo; Allan Taufiq Rivai (PT Dexa Medica, 2026)
Preeclampsia (PE) remains a leading cause of maternal and neonatal morbidity and mortality worldwide, affecting 2–15% of pregnancies. This review synthesizes recent advancements in the understanding of PE pathophysiology, includingplacental dysfunction, endothelial impairment, and novel biomarkers such as angiogenic factors. Drawing on global studies published up to 2025, we explore predictive models for early detection before 11 weeks of gestation, innovativemanagement strategies including aspirin prophylaxis, and disparities in maternal and neonatal outcomes. In Indonesia, where PE contributes to 26–30% of maternal deaths, we highlight local epidemiology, risk factors such as anemia and obesity, and tailored interventions to improve screening and care in resource-limited settings. By emphasizing evidencebasedpractices, this article underscores the need for integrated approaches to reduce the burden of PE and provides actionable insights for clinicians in both global and Indonesian contexts.